Corporate Governance and Firm Valuation in Colombia (2007)
This paper studies the separation of ownership and control of 108 listed companies in Colombia from 1996 to 2002, finding that voting rights are greater than cash flow rights because of indirect ownership across firms. The paper also examines the association of various ownership and control measures and separation ratios with a firm’s value and performance for the same sample of companies that traded their stock from 1998 to 2002. Large blockholders were found to exert a positive influence upon a firm’s valuation and performance, which validates the positive monitoring approach of large shareholders, but this relationship is not monotonic. The paper further reports results from a 2004 survey which suggests that Colombian firms have been slow to improve their corporate governance practices.